2022
DOI: 10.1038/s41598-022-12749-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of concurrently isolated primary microvascular endothelial cells, pericytes, and vascular smooth muscle cells from adult mouse heart

Abstract: The microcirculation serves crucial functions in adult heart, distinct from those carried out by epicardial vessels. Microvessels are governed by unique regulatory mechanisms, impairment of which leads to microvessel-specific pathology. There are few treatment options for patients with microvascular heart disease, primarily due to limited understanding of underlying pathology. High throughput mRNA sequencing and protein expression profiling in specific cells can improve our understanding of microvessel biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…Based on recent evidence, VSMCs seem to drive the inflammatory process of atherosclerosis 30 32 . We confirmed that the isolated cells were VSMCs by immunocytochemistry, using antibodies against the VSMC specific isoform of alpha-actin (Supplemental Figure 2A ) 33 35 . We performed a time course analysis to determine the effect of Ku80 deficiency on DSB formation and DDR activation in response to hydrogen peroxide exposure.…”
Section: Resultssupporting
confidence: 54%
“…Based on recent evidence, VSMCs seem to drive the inflammatory process of atherosclerosis 30 32 . We confirmed that the isolated cells were VSMCs by immunocytochemistry, using antibodies against the VSMC specific isoform of alpha-actin (Supplemental Figure 2A ) 33 35 . We performed a time course analysis to determine the effect of Ku80 deficiency on DSB formation and DDR activation in response to hydrogen peroxide exposure.…”
Section: Resultssupporting
confidence: 54%
“…Pre-warmed media is then added to cover the fragments completely. Explanted cultures are kept undisturbed for a few days until pericytes become visible as migrated cells from the tissue pieces ( 31 , 41 , 94 ). The advantages of this isolation technique are the increased yield of collected cells, low cost, and avoidance of the destructive stress caused by enzymes ( 95 ).…”
Section: Current Protocols For the Derivation Of Pericyte Populationsmentioning
confidence: 99%
“…The labeled cells are retained in the tube walls, and the unlabeled cells are discarded. MACS columns and Dynabeads are widely used to isolate pericytes due to the simplicity and rapidity of the procedure ( 32 35 , 94 , 103 ). The harsh magnetic field may cause damage or rupture of the cell membranes of fragile cells.…”
Section: Current Protocols For the Derivation Of Pericyte Populationsmentioning
confidence: 99%